Influence of boron on microstructure and mechanical properties of Gleeble simulated heat-affected zone in P91 steel. (December 2020) - Khajuria, Akhil; Akhtar, Modassir; Bedi, Raman; Kumar, Rajneesh; Ghosh, Mainak; Das, C.R.; Albert, Shaju K.
Abstract: In the present endeavor, a Gleeble thermo-mechanical simulator has been used to simulate subzones of the heat-affected zone (HAZ) of boron-free P91 and boron-modified P91B steels to investigate the influence of boron on microstructure and mechanical properties. The prior austenite grain (PAG) size remained similar to that of parent metal in the fine-grained heat-affected zone (FGHAZ) and inter-critical heat-affected zone (ICHAZ) of P91B steel. The microhardness value of simulated specimens, including parent metals was observed to be similar. But impression creep resistance of boron-containing steel was significantly higher than that of the boron-free steel. The presence of boron decreased precipitates size and increased fraction of low energy Σ3 coincident-site lattice (CSL) boundaries that attributed to improvement of creep resistance. However, there was a slight reduction in solid solution hardening due to increased area fraction of precipitates in parent metal and simulated specimens of boron-containing steel. Hindering of alloy element partitioning during impression creep of P91B-ICHAZ was observed, which was possibly due to the presence of boron in soluble form in the iron matrix and the segregated form on grain and sub-grain boundaries (SGBs). Further, the addition of boron was observed to retard M23 C6 precipitate coarsening in the P91B-ICHAZ in comparison to its P91 version. Highlights: For convincing interpretation of microstructure in HAZ subzones of P91 and P91B steels, Gleeble simulation was used. Impression creep and microhardness testing were used to establish structure-property correlation in HAZ subzones of both steels. Large and consistent fraction of low energy Σ3 CSL boundaries in FGHAZ and ICHAZ of P91B steel improved creep resistance. Reduction in solid solution hardening occurred in specimens of P91B steel due to increased area fraction of precipitates.